NEUROLOGICAL PHYSIOTHERAPY IN LABRADOR RETRIEVER DOG WITH PARAPARESIS: A CASE REPORT (International Journal of Physiotherapy, 2020)
Background: Spinal cord injuries (SCI) may cause neurological problems such as muscle weakness, sensory disorders, and incontinence. This case report aims to investigate the effectiveness of the sensorimotor rehabilitative physiotherapy program in a dog with paraparesis.Case Description: A 1-year-old, 27 kg male dog was brought to Near East University, Animal Hospital, after a motor vehicle accident. The dog was diagnosed as a T13 vertebral fracture and luxation at the T13-L1 spinal level according to the clinical and radiological examination performed by a veterinary physician. The dog showed; poor standing, weakness in the hind limbs and back muscles, urinary and fecal incontinence at the clinical examination. The physiotherapy program included; massage, sensory stimulation applications, Neuromuscular Electrical Stimulation (NMES), joint mobilizations, standing-balance exercises, and gait training.Outcome Measures: Consequently, improvements were obtained in standing and sitting balance, gait, bladder, and bowel functions at the end of the seven-week treatment period. The standing duration increased from 3 sec to >60 sec; also, thigh circumferences increased from 31cm to 36 cm in the right and 32 cm to 36 cm in the left limb. Canine Acute Pain Scale score was reduced from 2 to 1 in a positive sense.Conclusion: There were a satisfying motor and functional recovery in our case. We believe that the dog’s young age and the type of injury (neurapraxia) contributed to these positive results. Therewithal, early and active physiotherapy program plays a crucial role in maintaining functional independence, also coping with the symptoms in the dog.